2020
DOI: 10.1021/acssynbio.0c00114
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Inducible Genetic Switch for the Global Regulator WblA To Sustain Both Overproduction of Tiancimycins and On-Demand Sporulation in Streptomyces sp. CB03234

Abstract: The complex life cycle of streptomycetes is closely related to their secondary metabolisms, all controlled by cascade regulations. Tiancimycins (TNMs) are ten-membered enediynes possessing great potential for antitumor drug development. However, their low yields in Streptomyces sp. CB03234 have greatly limited subsequent studies. Through transcriptome analysis and genetic characterization, we proved that WblA is one pivotal global regulator to repress the biosynthesis of TNMs. The deletion of wblA could signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Comparative transcription analysis between a wild-type and a streptomycin-induced ribosome engineered TNMs high-producer CB03234-S exhibited that the wblA scb transcription level was relatively higher than those of other wbl genes (Zhang et al, 2020 ). To overcome the low titer issue of these compounds, the wblA sco ortholog named wblA scb (tentatively named here) was disrupted via homologous recombination, resulting in 13.9- and 1.7-fold increases of TNM-A in CB3234S and CB3234-S, respectively (Zhang et al, 2020 ). The production of TNLs, a group of main fermentation metabolites in CB03234, was also affected by the deletion of wblA scb .…”
Section: Wbla Orthologs In Other Streptomyces Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative transcription analysis between a wild-type and a streptomycin-induced ribosome engineered TNMs high-producer CB03234-S exhibited that the wblA scb transcription level was relatively higher than those of other wbl genes (Zhang et al, 2020 ). To overcome the low titer issue of these compounds, the wblA sco ortholog named wblA scb (tentatively named here) was disrupted via homologous recombination, resulting in 13.9- and 1.7-fold increases of TNM-A in CB3234S and CB3234-S, respectively (Zhang et al, 2020 ). The production of TNLs, a group of main fermentation metabolites in CB03234, was also affected by the deletion of wblA scb .…”
Section: Wbla Orthologs In Other Streptomyces Speciesmentioning
confidence: 99%
“…Since the existence of wblA scb is necessary for a spore formation but undesirable for TNMs overproduction, the NitR-ε-caprolactam (CPL) based inducible expression system for wblA scb was constructed in the CB03234 ΔwblA scb . This cell factory system successfully maintained the overproduction of TNMs without any additional processes and recovered the normal development of sporulation upon induction (Zhang et al, 2020 ).…”
Section: Wbla Orthologs In Other Streptomyces Speciesmentioning
confidence: 99%
“…In this study, we deleted the regulatory gene wblA gh from the chromosome of S. ghanaensis O1∆H5 using the aforementioned marker-and "scar"-less technique. The wblA orthologs are conserved across the Streptomyces genus and many studies, including that for Mm synthesis, reported them as negative regulators of antibiotic production [31][32][33]. Deletion of wblA gh strongly increased NoA accumulation by the resulting triple mutant strain S. ghanaensis O1∆H5∆wblA, while completely blocking the morphogenesis at the aerial mycelium level.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study in Streptomyces coelicolor also demonstrated a capacity of AdpA to inhibit the chromosome replication at the initial stage by binding to the replication origin (oriC), thus decreasing the access of the initiator protein (DnaA) [29]. Furthermore, deletion of wblA, a gene encoding a small Fe-S-containing cluster regulatory protein, drastically affects the antibiotic biosynthesis in many streptomycetes, including Mm production [18,24,[30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Organisms are naturally capable of producing metabolites with antimicrobial characteristics. Unfortunately, “wild-type” antibiotic producers have poor production and low titers; however, with the unravel of novel biosynthesis mechanisms of that produce antibiotics and the tools provided by synthetic biology, it is possible to engineer the capacities of organisms to over-produce and diversify these metabolites ( Breitling and Takano, 2015 ; El Karoui et al, 2019 ; Zhang et al, 2020 ).…”
Section: Genetic Engineering To Modify Antibioticsmentioning
confidence: 99%